Studying the Dietary Habits of Seafood Consumption among Saudis and Residents in the Province of Delam at Prince Sattam bin Abdulaziz University - Al- Moaleem, Maalem Haasan (Journal of medical and pharmaceutical sciences, 2019)
This study was conducted in order to identify the dietary habits of fish consumption in the province of Delam in Saudi Arabia where four hundred and fifty questionnaire were distributed to the employees of Prince Sattam bin Abdulaziz University during the month of Rabee I until Rajab 1440H. The results of the analysis in three hundred answered questionnaire showed that the sample of Saudis was (84.7%) and the percentage of university education (68.7%). The study showed that fish meat ranked third in the preference for meat types and that the fresh fish is preferred in the purchase followed by canned fish. The preferred types of fish are shrimp, grouper, kennad, net, poetic, nagel, and white. Moreover, the study confirmed that (46.3%) of individuals prefer to eat it once a week, cooked at home, and grilled. Furthermore, preferred side dish with fish was fried potatoes. The study indicates that the percentage of fish consumed by non- Saudis is higher which was twice in the week for non- Saudis and once a week for Saudis. This may be due to different dietary habits among individuals or the impact of prices, consumption habits, or distance from the coast. The study concluded the need for further studies to educate individuals about the benefits of fish and the importance of Public Health.